Productivity effects of processing and ordinary export market entry: a time-varying treatments approach - Girma, Sourafel,Görg, Holger (Kiel Centre for Globalization, 2021)
China's policy of encouraging export processing has been the topic of much discussion in the academic literature and policy debate. We use a recently developed econometric approach that allows for time varying
10419/232952
Keywords: Graue Literatur; export processing; firm performance; China; time varying treatments